Pengaruh Treatment Sport Massage Terhadap Pemulihan Delayed Onset Muscle Soreness (DOMS) Pasca Aktivitas Fisik Pada Pemain Futsal Tim SMKN 1 Driyorejo - Sevtian Dimas Akhmad Alfaris; Joesoef Roepajadi; Ananda Perwira Bakti; Abdul Aziz Hakim (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
Futsal is a sport that is carried out with high intensity and involves movements that give rise to eccentric contractions, causing stiffness and increased pain in the muscles or called DOMS. This causes SMKN 1 Driyorejo futsal players to experience complaints of muscle pain and limited joint mobility due to DOMS. Efforts are needed to overcome these complaints, one of which is with Sport Massage. This study aims to determine the effect of Sport Massage treatment on the recovery of Delayed Onset Muscle Soreness after physical activity in futsal players of SMKN 1 Driyorejo team. The types of exercises performed in this study as DOMS inducers include squat jump, high knee, jump lunges, and single leg lateral jump. The pretest data collection time was carried out 2 days after the sample performed the exercise. Sport Massage was performed on day 3 on the lower extremities by observing the research SOP that has been given including the frequency of treatment 1 time and manipulation in the form of effleurage, petrissage, walken, and shaking with a massage duration of 20 minutes per sample. Posttest data will be taken the next day after the sample is given a Sport Massage.This research is quantitative with pre-experimental method and one group pretest-posttest design with a sample of 23 futsal players of SMKN 1 Driyorejo team. Based on the analysis of the statistical description of the initial data (pretest) obtained an average of 7.17 with a minimum value of 5 and a maximum value of 9 and a standard deviation of 0.984. While the final data (posttest) obtained an average of 2.26 with a minimum value of 0 and a maximum value of 4 and a standard deviation of 1.010. To determine whether there is a significant effect of Sport Massage treatment on DOMS recovery, a hypothesis test is conducted using Independent Sample T-Test. The test criteria are if the significance value (2-tailed) < 0.05 then H0 is rejected and Ha is accepted, while if the significance value (2-tailed) > 0.05 then H0 is accepted and Ha is rejected. The results of testing the hypothesis of this study obtained a mean value of 4.913 with a standard error of 0.294 and a significance value (2-tailed) of 0.000 <0.05, thus H0 is rejected and Ha is accepted so it is concluded that there is a significant effect of pretest and posttest data on the treatment of Sport Massage on the recovery of Delayed Onset Muscle Soreness after physical activity in futsal players of the SMKN 1 Driyorejo team.